Antibacterial and Antifungal Activities of New Acylated Derivatives of Epigallocatechin Gallate - Matsumoto, Yoshimi; Kaihatsu, Kunihiro; Nishino, Kunihiko; Ogawa, Miho; Kato, Nobuo; Yamaguchi, Akihito (Frontiers in Microbiology, 2012)
(-)-Epigallocatechin-3-O-gallate (EGCG) has useful antiviral, antimicrobial, antitoxin, and antitumor properties. Previously, Mori, S. et al. (Bioorg Med Chem Lett 18:4249-4252, 2008) found that addition of long acyl chains (C16–18) to EGCG enhanced its anti-influenza virus activity up to 44-fold. The chemical stability of EGCG against oxidative degradation was also enhanced by acylation. We further evaluated the in vitro activity spectrum of the EGCG derivatives against a wide range of bacteria and fungi. A series of EGCG O-acyl derivatives were synthesized by lipase-catalyzed transesterification. These derivatives exhibited several-fold higher activities than EGCG, particularly against Gram-positive organisms. Antifungal activities of the derivatives were also 2 to 4-fold superior to those of EGCG. The activities of the EGCG derivatives against Gram-negative bacteria were not distinguishable from those of EGCG. Among the derivatives evaluated, MICs of dioctanoate, palmitate (C16), palmitoleate, and linolenate for 17 Staphylococcus aureus strains were 4–32 μg/ml, although MIC of EGCG for these 17 strains was >128 μg/ml. C16 demonstrated rapid bactericidal activity against MRSA at 25 μg/ml. The enhanced activity of C16 against S. aureus was supported by its increased membrane permeabilizing activity determined by increased SYTOX Green uptake. The EGCG derivatives were exported by the efflux pump AcrAB-TolC of Escherichia coli. The tolC deletion mutant exhibited higher sensitivity to C16 than to EGCG. Addition of long alkyl chains to EGCG significantly enhanced its activities against various bacteria and fungi, particularly against S. aureus including MRSA. C16 would be an alternative to antibiotics and disinfectants.